Academics’ perceptions on online continuous professional development in higher education - Simelane-Mnisi, Sibongile (The Independent Journal of Teaching and Learning, 2023)
This study aimed to investigate academics’ perceptions of online continuous professional development (OCPD) and the design and development of online modules in higher education. Fourteen academics from one faculty at the University of Technology in South Africa participated. In selecting the participants for this study, purposive and convenient sampling was applied. A qualitative case study approach was used. Data were collected through semi-structured interviews and open-ended questionnaires. Saldaña’s thematic approach to analysis was used to analyse data using Atlas.ti. It was found that most of the academics who attended OCPD were able to build their module on IMFUNDO because the instructional designer provided the module structure or template. The findings revealed that the university’s eChampions contributed immensely during the process by providing additional support in the departments. It is recommended that further studies be conducted on the students’ perceptions of implementing the IMFUNDO modules developed in this study.